2014
DOI: 10.1016/j.msard.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A is not associated with exacerbations in multiple sclerosis

Abstract: We did not find evidence for a role for vitamin A in the disease course of RRMS. We did find an association between vitamin A and D levels in the RRMS patients, possibly explained by dietary products that contain both fat-soluble vitamins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
10
1
2
Order By: Relevance
“…In the neuroinflammatory context of MS, RA showed various beneficial effects [ 95 ]. In clinical trials, supplementation of RA was not correlated with MS exacerbation [ 96 ]. On the contrary, RA enhanced the overall quantitative assessment or MS functional composite of relapsing–remitting MS patients [ 97 ].…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…In the neuroinflammatory context of MS, RA showed various beneficial effects [ 95 ]. In clinical trials, supplementation of RA was not correlated with MS exacerbation [ 96 ]. On the contrary, RA enhanced the overall quantitative assessment or MS functional composite of relapsing–remitting MS patients [ 97 ].…”
Section: Efficacies Of Ra In the Treatment Of Autoimmune Diseasesmentioning
confidence: 99%
“…VitA improved the function of astrocytes, led to remyelination, and suppressed immune function in MS patients [218,269,[274][275][276][277]. In contrast, results from one study demonstrated no correlation between serum VitA concentration and the progression of MS [278].…”
Section: Vitamins In Multiple Sclerosismentioning
confidence: 91%
“…However, they have reported a positive correlation between vitamin A and vitamin D serum level, which might be due to the patients' diet. Accordingly, it has been suggested that retinoic acid has tissue specific manner and its local production in CNS might cause relapse courses [57] , [58] . Based on these population studies, vitamin A can be considered as a significant micronutrient in pathophysiology of the disease more extended studies are needed for a strong conclusion.…”
Section: Fat Soluble Vitaminsmentioning
confidence: 99%